The Robarts lute book c. 1654-68 for 11-course French lute in D minor tuning - Spencer, Robert 1932-1997; Rastall, Richard (Kilkenny Boethius Press, 1978)
Facsim. of a 17th century French lute music ms. acquired by Hender Robarts in the 1650's or 1660's.Principal identified composer is Ennemond Gaultier; the repertory, chiefly dance pieces, "is representative of the best French lute music of the 1640s and 1650s"--Introd.Introd. precedes and ms. inventory follows facsim.